(untitled) (Krzysztofory. Zeszyty Naukowe Muzeum Historycznego Miasta Krakowa, 2026)
RIGHT-BANK CRACOW. HISTORIC AND SCENIC CHANGES IN CRACOW ŁAGIEWNIKI Łagiewniki is a former village, once some four kilometres south of Cracow, then incorporated into Cracow as a district. Since as early as the Middle Ages, settlement has been going on in the southern part of the village along the Wilga River bed, as confirmed by archeological findings from this area. From the 11th century Łagiewniki was a settlement providing services to the duke’s castle at Wawel Hill. In the 14th century settlement reached the castle area near today’s Sobótka and Myślenicka streets. At the end of the 15th century and from the mid-16th century the village belonged to the Cracow Castellany. The first reference to the Łagiewniki castle is from the 16th century; a trade route from Cracow to Hungary passed near the castle. During the First Partition of Poland (1772) Łagiewniki fell under the Austrian occupation and was incorporated into the so called „Ekonomia Myślenicka”. From that time to 1939 the village was in the hands of private owners, including the Baruch family (second half of the 19th century). Over the 19th century the village evolved from a traditional agricultural seltlement with some additional crafts into a housing suburb with industrial role (1st half of the 20th century). The present character of Łagiewniki was determined by the location of factories and industrial plants, mostly connected with the construction materials industry (the Baruch family’s brick and tile factories, gypsum mines, ceramics plants). The dominant element of the village landscape since the end of the 19th century has been the cloister of the Sisters of the Holy Mother of Charity. A cemetery for the soldiers of the First World War adjoins the wall of the cloister complex. Now Łagiewniki is composed of three urban complexes: the Cegielniania neighnourhhod, Łagiewniki (historic centre) and Wola Duchacka Zachód. The southern part is covered with the industrial waste dumps of the Soda Plant in Borek Fałęcki; the landscape of this part of the village have been disfigured and the picturesque environs of the Wilga River have been ruined. The beauty of the landscape has been affected by new buildings, large in size and uninteresting in form, erected beside semi-detached houses from the 1930s. New urban elements foreign to the local tradition, were introduced when housing estates of high apartment blocks were built. Despite the continuing process of urbanization, and at the same time deterioration, Łagiewniki has reserved some elements of its historic medieval town layout, historic houses and complexes. Such a complex is the district centre, with a palace (end of the 19th century), manor house and auxilary outbuildings; the complex replaced the initial 15th-century manorial and agricultural estate. Nearby are buildings from the beginning of the 20th century (a school from 1906) near the manor, serving for small-business, services and educational purposes. In the vicinity of Strumienna and A. Fredry Streets is an enclave of wooden country architecture from the 1920s.